The influence of microbial-based inoculants on N2O emissions from soil planted with corn (Zea mays L.) under greenhouse conditions with different nitrogen fertilizer regimens - Calvo, Pamela; Watts, Dexter B; Kloepper, Joseph W; Torbert, H. Allen (Canadian journal of microbiology, 2016)
Nitrous oxide (N 2 O) emissions are increasing at an unprecedented rate owing to the increased use of nitrogen (N) fertilizers. Thus, new innovative management tools are needed to reduce emissions. One potential approach is the use of microbial inoculants in agricultural production. In a previous incubation study, we observed reductions in N 2 O emissions when microbial-based inoculants were added to soil (no plants present) with N fertilizers under laboratory incubations. This present study evaluated the effects of microbial-based inoculants on N 2 O and carbon dioxide (CO 2 ) emissions when applied to soil planted with corn (Zea mays L.) under controlled greenhouse conditions. Inoculant treatments consisted of (i) SoilBuilder (SB), (ii) a metabolite extract of SoilBuilder (SBF), and (iii) a mixture of 4 strains of plant-growth-promoting Bacillus spp. (BM). Experiments included an unfertilized control and 3 N fertilizers: urea, urea – ammonium nitrate with 32% N (UAN-32), and calcium – ammonium nitrate with 17% N (CAN-17). Cumulative N 2 O fluxes from pots 41 days after planting showed significant reductions in N 2 O of 15% (SB), 41% (BM), and 28% (SBF) with CAN-17 fertilizer. When UAN-32 was used, reductions of 34% (SB), 35% (SBF), and 49% (BM) were obtained. However, no reductions in N 2 O emissions occurred with urea. Microbial-based inoculants did not affect total CO 2 emissions from any of the fertilized treatments or the unfertilized control. N uptake was increased by an average of 56% with microbial inoculants compared with the control (nonmicrobial-based treatments). Significant increases in plant height, SPAD chlorophyll readings, and fresh and dry shoot mass were also observed when the microbial-based treatments were applied (with and without N). Overall, results demonstrate that microbial inoculants can reduce N 2 O emissions following fertilizer application depending on the N fertilizer type used and can enhance N uptake and plant growth. Future studies are planned to evaluate the effectiveness of these microbial inoculants in field-based trials and determine the mechanisms involved in N 2 O reduction.